Urgensi Lingkungan Bisnis Dan Strategi Dalam Menciptakan Keunggulan Kompetitif - Lena Ellitan (BIP's JURNAL BISNIS PERSPEKTIF, 2021)
This study has several main objectives as follows: (1) To explore how SMEs develop strategies based on their strengths, weaknesses, opportunities, and challenges. (2) Explore the various efforts of SMEs in anticipating the uncertainty of the business environment. (3) Exporting the efforts of SMEs to formulate their competitive strategies. (4) Exploring how environmental uncertainty affects the choice of a SMEs competitive strategy. (5) Explore the efforts of SMEs to formulate their operational strategies. (6) Exploring how competitive strategy affects SME operational strategies. (7) Exploring how competitive strategy and operating strategy affects SMEs business performance. This study uses a descriptive research approach that seeks to identify and map (mapping) the potential and characteristics of SMEs in Surabaya and its surroundings (Sidoarjo, Gresik) with the aim of obtaining an accurate and detailed descirption of the potential characteristics of small and medium enterprises in the Surabaya area and surroundings. Based on the phenomena found in this study, there are several things that can be underlined: uncertainty in the business environment does not affect the company’s business strategy. In carrying out their business strategy, SMEs usually use the following strategis: (1) Concering the development of skills to respond to the opportunities created by companies in the first market. What often happens is that many imitators improve or modify goods and services to create higher value for buyers. If so, entrepreneurs need to shift their competitiveness to other market segments by dominating small market segments that large companies sess as having no oppurtunity. (2) Changes in product, market, or industry characteristics based on innovation. This strategy is carried out by changing existing products and services, for example changing benefits, values, and other economic characteristics.